Political Aspects of Religion, Religious Freedom and Religious Tolerance at the Time of the Emperor Constantine and Today - Крстић, Зоран Г (Sabornost - The Theological Year-book, 2013)
The author in this paper considers, compares and analyzes the religious tolerance of the Equal to the Apostles Emperor Constantine, expressed in the Edict of Milan along with the current understanding of religious tolerance. A sketch of reasons for emergence of modern religious tolerance is exposed, and its relationship and dependence on political aspects of religion, both in ancient and medieval societies, as well as today. The author also discusses specific contemporary relationship to the truth which gives rise to the transformation of religious tolerance into religious freedom of an individual that is characteristic for modern society but not that of Constantine. In conclusion, the author believes that the beginning of the road that leading to today’s social achievements in the field of religious freedom, is the Edict of Milan of the year 313.